Prospective Unemployment and Interstate Population Movements: A Reply - Blanco, Cicely W. (The Review of Economics and Statistics, 1965)
sion equation presented in the note, in which x appears as an independent variable. Therefore, the high correlation between migration and prospective unemployment may be misleading. It may be, in effect, merely a correlation of the dependent variable with itself. On the basis of the foregoing, it would appear that the problem of establishing a strong link between migration and job opportunities may not really have been solved by introducing the new concept of unemployment. Nevertheless, Dr. Blanco's ingenious approach to the problem will be of considerable interest to anyone concerned with the determinants of population movements.